Educational continuity following the 2013 Colorado Front Range Floods: a case study of Lyons elementary and middle/senior high schools - Tobin, Jennifer Lynn, author; Peek, Lori, advisor; Hempel, Lynn, committee member; Browne, Katherine, committee member; Carlson, Laurie, committee member; Cox, Robin, committee member (Colorado State University. Libraries, 2019)
Educational continuity is a complex social process where school, school district, and community leaders work together to continue providing education and all other school-based services for students following a disaster. Schools are vital social institutions that serve a variety of functions for students and communities and are integral to post-disaster response and recovery activities. Moreover, schools can offer protective mechanisms when they continue to care for and educate students following a crisis. However, current literature pays little attention to the organizational capacity of school districts to respond to disasters and what district-and school-level characteristics create the context for educational continuity. This research begins to fill this gap by exploring how the St. Vrain Valley School District (SVVSD) prepared for, responded to, and continued to educate Lyons students following the 2013 Colorado Front Range Floods. This dissertation draws from organization theory, school management, and disaster sociology literatures to frame the educational continuity process for Lyons Elementary and Middle/Senior High Schools. The research questions that guide this dissertation are: 1) How did Lyons Elementary and Middle/Senior High Schools and the St. Vrain Valley School District keep students and staff together after the 2013 Colorado Front Range Floods? 2) What was the pre-existing social context that allowed school administrators to prioritize educational continuity for Lyons students? and 3) What resources were needed and what actions were taken by Lyons Elementary and Middle/Senior High School staff to continue operations and assist students in recovering from the disaster? To answer these questions, I conducted a qualitative case study that included: 1) semi-structured in-depth interviews with 67 key community leaders, district administrators, school administrators, teachers, counselors, parents, and students involved in the educational continuity process; and 2) the analysis of secondary data in the form of preparedness plans, student created photo and story books, demographic information, and official and personal documents generated in response to the flood. Findings from this dissertation research revealed five major influences that contributed to educational continuity for Lyons students. First, the school district purposefully dedicated time and resources to preparedness planning. This included employing a full-time emergency manager who developed and carried out critical training exercises prior to the flood. The knowledge gained from these activities contributed to the capacity of the school district to swiftly resume classes for students at a new location just eleven days after floodwaters displaced Lyons residents. Second, the school district had a well-established organizational ethos that was built on distributed control, dedication to students, strong social bonds, and a reciprocity of trust between and across organizational members. Third, this organizational ethos was developed with and supported by the superintendent of the district, who had a documented history and lauded reputation of being a strong and compassionate leader with years of experience. Fourth, parents, teachers, staff, and administrators were dedicated to helping students recover. School level efforts to facilitate recovery included establishing routine and stability, allowing space for flexibility and adaptability, and implementing the use of creative methods such as art and storytelling. Fifth, the above efforts were, in part, made possible because of the socioeconomic and demographic characteristics of the school district and the community of Lyons. The SVVSD has a robust fiscal budget that provided the immediate financial resources necessary to reopen school quickly. The district and school staff are highly educated, well-trained, and have many years of experience, which made them well-equipped to respond to this event. Furthermore, like the demographics of the school district, Lyons is a mostly white, educated, upper-middle class community. Therefore, community leaders and families were able to draw upon their own education and social, cultural, and material resources to help facilitate the smooth transition and educational continuity process for Lyons students. This dissertation operationalizes the concept of educational continuity and offers clear examples for how to plan for this process. Further, it contributes theoretically by advancing understanding of how preexisting organizational structures and management styles influence disaster recovery. Based on the findings from this research, I argue that schools and school districts should be more formally integrated into community level disaster preparedness and response frameworks and better utilized as emergent organizations when disasters strike. Finally, this dissertation contributes methodologically, by offering an in-depth case study for school district emergency managers to draw from when creating their own educational continuity plans. This work also reveals the need for more research to examine and measure preparedness, response, and recovery efforts and the organizational capacity of schools across a variety of locations and social contexts.
Keywords: educational continuity; leadership; school displacement; emergency preparedness; disaster; organization sociology